2017
DOI: 10.3390/ijms18020359
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a DHA Signature in the Lipidome and Metabolome of Human Hepatocytes

Abstract: Cell supplementation with bioactive molecules often causes a perturbation in the whole intracellular environment. Omics techniques can be applied for the assessment of this perturbation. In this study, the overall effect of docosahexaenoic acid (DHA) supplementation on cultured human hepatocyte lipidome and metabolome has been investigated using nuclear magnetic resonance (NMR) in combination with traditional techniques. The effect of two additional bioactives sharing with DHA the lipid-lowering effect—propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…According to Vauzour et al (2015) [ 64 ], the additive effect of C3G and PCA cannot be ascribed to an increased DHA intracellular concentration due to enhanced DHA synthesis from precursors. As well, in a recent study we observed neither an increased DHA concentration in hepatic cells supplemented with PRO, nor an additional increase of DHA concentration in cell supplemented with DHA plus PRO compared to DHA alone [ 65 ].…”
Section: Discussionmentioning
confidence: 78%
“…According to Vauzour et al (2015) [ 64 ], the additive effect of C3G and PCA cannot be ascribed to an increased DHA intracellular concentration due to enhanced DHA synthesis from precursors. As well, in a recent study we observed neither an increased DHA concentration in hepatic cells supplemented with PRO, nor an additional increase of DHA concentration in cell supplemented with DHA plus PRO compared to DHA alone [ 65 ].…”
Section: Discussionmentioning
confidence: 78%
“…Recently, several meta-analyses established that n-3 LCPUFA supplementation (especially DHA) is useful in the dietary management of patients with NAFLD (adults and children), but additional trials are needed to better understand the effects of n-3 LCPUFA on histological outcomes in patients with NASH [88][89][90][91]. Additionally, new omics techniques have proven the beneficial effects of DHA (alone or co-administrated with other products) on hepatocyte lipidome [92]. These antecedents and the molecular mechanisms discussed for DHA and HT co-administration warrant future studies in NAFLD patients, to attained liver steatosis resolution, thus avoiding its progression into more unmanageable stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Ghini and co-workers showed that supplementing culture medium with 22:6n-3 [docosahexaenoic acid (DHA)] affected both the lipidome and metabolome of HepG2 hepatoma cells. Owing to the supplement, the total contents of cholesterol, SFAs and MUFAs decreased, whereas the PUFA and TAG contents of the cells increased ( Ghini et al, 2017 ). In our study, 22:6n-3 was present at a very low level in media A, B and C, and present mainly in medium D, used during the late hepatic maturation.…”
Section: Discussionmentioning
confidence: 99%